Evaluation of hollow fiberoptic tips for the conduction of Er : YAG laser - Vieira Alves, Paulo Roberto; Aranha, Norberto [UNESP]; Alfredo, Edson; Marchesan, Melissa Andréia; Brugnera Júnior, Aldo; Sousa-Neto, Manoel D. (Mary Ann Liebert, Inc., 2005)
Objective: The use of Er:YAG laser operating in the 3 μm range with adjustable power and pulses has become popular for dental and medical practice due to its high photoablative capacity, surgical precision and antimicrobial action. Background data: The existing fiberoptic tips irradiate lasers parallel to the long axes of the tooth limiting its efficiency in the root canal. Methods: We evaluated hollow fiberoptic tips obtained from silicate glass as a means of Er:YAG laser conduction in dental procedures. The fiber tips were molded from capillary tubes with different profiles so that their ends would have cylindric, conical or spherical shapes. The performance of the three fibers as a means of propagation of Er:YAG (λ = 2.94 μm) laser radiation was compared to that of a solid sapphire fiber at 10 Hz and 200 mJ and of 20 Hz and 500 mJ. The profiles of frontal and lateral burning were visualized on thermal paper. Results: Analysis of these profiles demonstrated that the sapphire tip and the hollow fiber of cylindric section did not differ significantly in the profiles of frontal burning, and no lateral burning was detected. The fibers of the conical and spherical sections, although presenting attenuation in the frontal output power, showed a larger burning area in the frontal profile, in addition to producing lateral burning. Conclusions: The results indicate that commercial hollow fiberoptics have advantages such as easy manufacture of the different tip shapes, great adaptability, low cost, and a low loss of transmission. © Mary Ann Liebert, Inc.
Keywords: Capillarity; Dentistry; Erbium; Health care; Laser ablation; Laser pulses; Medical problems; Microorganisms; Surgery; Yttrium compounds; Hollow fibers; Medical practice; Solid sapphire; Surgical precisions; Fiber optics; Antimicrobial activity; Dentistry; Endodontics; Erbium YAG laser; Fiber optics; Tthermal analysis; Tooth root canal; Aluminum Oxide; Equipment Design; Fiber Optics; Glass; Laser Surgery; Physics; X-Ray Diffraction